Characterization of HEC/PANI Film as a potential electroactive packaging with pH sensor - Nooranis Mustapha,; Nozieana Khairuddin,; Ida Idayu Muhamad,; Shahrir Hashim,; Md. Bazlul Mobin Siddique, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Interest in the use of intelligent packaging systems for food products has increased in recent years. Intelligent packaging systems are those that monitor the condition of packaged foods to give information regarding the quality of the packaged food during transport and storage. The potential of HEC/PANI film as pH indicator and pH sensor were evaluated. HEC/PANI film was prepared by solution blending and casting method. Fourier transform infrared (FTIR) spectroscopy showed that there was no chemical interaction between HEC and PANI. The film properties were retained chemically. The electrical conductivity increment from 1.14×105 to 2.2 ×105 S/cm was observed when PANI was incorporated into the HEC film matrix. Field emission scanning electron microscopy (FESEM) showed that the electrical conductance network of PANI was formed in HEC/PANI film. The electrical sensitivity of the film has been studied with I-V characterization. The changes in color and current of HEC/PANI film on interaction to pH buffer 1-14 shows its suitability as pH indicator and pH sensor for food.